Pengaruh Pendapatan Asli Daerah dan Belanja Modal terhadap Pertumbuhan Ekonomi (Studi pada Kabupaten/Kota di Pulau Sumatra) - . Yuliana (Jurnal Akuntansi dan Keuangan, 2014)
This study aimed to examine the effect of revenue and capital expenditure on economic growth, studies on district / city on the island of Sumatra. The independent variables were the PAD and Capital Expenditures. While the dependent variable is economic growth. The data used is secondary data obtained from the Central Statistics Agency www.djpk.depkeu.go.id and district / city on the island of Sumatra from 130 population and that meet the criteria of 30 samples. Based on the research results, it was concluded that 1) Revenue positive effect on Economic Growth 2) Capital Expenditures positive effect on economic growth.